THE EFFECT OF GINGER AROMATHERAPY ON REDUCING THE FREQUENCY OF NAUSEA AND VOMITING IN FIRST TRIMESTER PREGNANT WOMEN IN THE KEPENUHAN HEALTH CENTER WORK AREA - Junita, Elvira; Andriana; Seswita , Lise (INTERNATIONAL JOURNAL OF MIDWIFERY AND BEAUTY, 2025)
Nausea and vomiting during pregnancy typically occur between the 4th and 8th weeks of gestation and may persist until the 14th to 16th week. These symptoms are experienced by approximately 70-80% of pregnant women. Among various herbal aromatherapies, ginger aromatherapy is considered the most effective and offers several advantages for pregnant women experiencing nausea and vomiting compared to other herbal options. This study employed a pre-experimental research design using a One-Group Pretest-Posttest Design, conducted from March 20 to April 20, 2023. A total of 32 participants in their first trimester of pregnancy, residing in the working area of Kepenuhan Public Health Center, were provided with ginger aromatherapy to assess its effectiveness in reducing nausea and vomiting. The analysis of the data revealed that after the intervention, the majority of participants (24 pregnant women or 75%) reported no further nausea and vomiting, while 8 participants (25%) continued to experience these symptoms. The statistical analysis yielded an Asymp. A sig value of 0.042, indicating that p < 0.05, leads to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). These findings that the application of ginger aromatherapy is effective in significantly reducing the frequency of nausea and vomiting among first-trimester pregnant women in the working area of Kepenuhan Public Health Center in 2023.